2007
DOI: 10.1038/sj.bjc.6603827
|View full text |Cite
|
Sign up to set email alerts
|

The significance of proline-rich tyrosine kinase2 (Pyk2) on hepatocellular carcinoma progression and recurrence

Abstract: Understanding the precise molecular mechanisms that trigger liver cancer cell migration and invasion could develop novel therapeutic strategies targeting cancer cell invasion to increase the sensitivity to current treatment modalities. In the current study, 49 patients with hepatocellular carcinoma (HCC) were included prospectively. Liver tumour and adjacent non-tumour tissues were detected for the expression of Proline-rich tyrosine kinase 2 (Pyk2), focal adhesion kinase (FAK), ezrin and fibronectin at protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 22 publications
4
64
0
Order By: Relevance
“…5 such a correlation between FAK levels and the invasive phenotype in breast cancer. 38 In a similar manner, elevated Pyk2 expression was found to correlate with the progression of hepatocellular carcinoma, 39 gastric carcinoma, 40 and astrocytomas. 41 In contrast, other studies reported rather decreased Pyk2 expression in advanced osteosacroma 42 and in high-grade prostate cancer compared with normal epithelial prostate tissue and benign prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 75%
“…5 such a correlation between FAK levels and the invasive phenotype in breast cancer. 38 In a similar manner, elevated Pyk2 expression was found to correlate with the progression of hepatocellular carcinoma, 39 gastric carcinoma, 40 and astrocytomas. 41 In contrast, other studies reported rather decreased Pyk2 expression in advanced osteosacroma 42 and in high-grade prostate cancer compared with normal epithelial prostate tissue and benign prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 75%
“…PYK2 is mainly expressed in the central nervous system and hematopoietic cells; however, lines of evidence indicated the elevated expression of PYK2 in malignant tumors of epithelial origin. In hepatocellular carcinoma and nonsmall cell lung cancer, overexpression of PYK2 is found in approximately 60% of tumors evaluated and is significantly correlated with poor prognosis or lymph node metastasis (Sun et al 2007, Zhang et al 2008. In breast and bladder cancers, the expression of PYK2 elevated in malignant lesions compared with benign tissues (Behmoaram et al 2008, Genua et al 2012.…”
Section: :8mentioning
confidence: 99%
“…As a member of the focal adhesion kinase family, FAK2 has been reported to be mainly localized at the focal adhesions and nuclei of cells (48). Autophosphorylation at tyrosine residue Y402 activates FAK2, which then functions as a docking site for the SH2 domain of Src (49).…”
Section: Activation Of Focal Adhesion Kinases In Tamoxifenmentioning
confidence: 99%